Manajemen perubahan perguruan tinggi pada saat pandemi Covid-19 - Pandu Adi Cakranegara (Studi Ilmu Manajemen dan Organisasi, 2020)
Purpose: The purpose of this research is to apply an online learning framework toward Indonesia Higher Education institution. The research is using change management approach with Anderson learning framework. Research methodology: This research is an analysis of the literature and data available at the time of the pandemic. By collecting various data and existing literature, an analysis is made of how this challenge can be an opportunity for education in Indonesia to be able to move forward in the future. Results: The results of this study show that in Indonesia not only geographical divide but also digital divide. The root of the problem of this digital divide is economic inequality, one of which is due to infrastructure inequality. Limitations: This research is unable to apply the Anderson model to all the learning conditions in Indonesian. Instead it is choosing some sample to apply the model. Contribution: This research contribution is the adjusment of Anderson model so it can be applied in Indonesian context. Keywords: Pandemic, Change management, Online learning model